Wood to Energy: Use of the Forest Biomass for Wood Pellets - Marian Marinescu; Todd Bush (EDIS)
FOR-207, a 4-page illustrated fact sheet by Marian Marinescu and Todd Bush, is part of the Wood to Energy series. It introduces the use of wood pellets as a renewable energy source — current and new feedstock sources, feasibility, and research needs. Includes references. Published by the UF School of Forest Resources and Conservation, February 2009.